The pocket lawyer for comic books a legal toolkit for indie comic book artists and writers - Crowell, Thomas A. (Focal Press, 2015)
"Focal Press' Pocket Lawyer series serves as a legal toolkit for independent producers and artists in the creative industries.The Pocket Lawyer for Comic Book Creators is designed to help emerging artists and veteran professionals in the comic book industry build a solid foundation of business and communication practices that they need to thrive in today's ever-changing, uncertain world of indie comics. Readers will learn to protect their trademarks, hire artists so everyone wins, and learn the ins and outs of contracts with this helpful resource. *Follow along with a comic book to help you get through those tough-to-grasp concepts. Watch as J.D. Esquire, Hero at Law combats with Collaboration Saboteur and other ne'er do wells. *Learn the legal ins and outs of all jobs applicable to the comic book industry: writer, inker, penciller, creator. *Decipher the cryptic languages of the contract, protect your precious intellectual property, and leap over legal obstacles in a single bound"--